How Effective Are the Canine Visceral Leishmaniasis Vaccines Currently Being Tested in Dogs? A Systematic Review and Meta‐Analysis - Pádua, Josiane Aparecida Martiniano (Parasite Immunology, 2025)
ABSTRACT Canine visceral leishmaniasis (CVL) is a zoonotic disease of great worldwide importance and can be prevented by vaccinating seronegative dogs. The objective of the present systematic review and meta‐analysis is to verify the efficacy rate of vaccines tested in dogs against CVL or L. infantum infection. We used PRISMA guidelines for this review and Pubmed, Web of Science, Scopus, Cochrane, Scielo and CABI to find studies about vaccines against CVL in dogs. Articles were analysed and grouped according to the antigens used. The risk of bias analysis was performed using SYRCLE's RoB tool and meta‐analysis using R Statistical language. The final analysis was conducted using 22 studies that assessed DNA, excreted/secreted proteins and subunit vaccines, involving a total of 92 animals, 96 animals and 78 animals, respectively. Regarding DNA vaccines, the analyses revealed non‐significant results in terms of preventing parasite presence in the organs or the onset of clinical signs. However, subunit vaccines demonstrated statistically significant results concerning parasite presence in the organs, but not when it comes to clinical signs. Additionally, there was no statistically significant difference observed in parasite burden in the organs or clinical signs for the excreted/secreted vaccines. The meta‐analysis indicated that subunit and excreted/secreted protein vaccines were significantly more effective in preventing parasites in vaccinated animals compared to both DNA‐based vaccines and control groups. Heterogeneity among studies is a limitation, emphasising the need for standardised protocols for reliable comparisons.